Penerapan Model ASSURE dengan Media Mentimeter untuk Meningkatkan Motivasi Belajar Bahasa Indonesia Siswa Kelas V SDN Percobaan 1 Malang: Penelitian - Yusron Izza Rohmani; Esti Untari; Dwi Windari (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the implementation of the ASSURE Model with the Mentimeter media in teaching Bahasa Indonesia for fifth-grade students at SDN Percobaan 1 Malang, as well as to examine its effect on students' learning motivation. The research approach used is descriptive qualitative with a case study design. The subjects of this study are 29 fifth-grade students, with instruments including interviews, questionnaires, and pretest-posttest. The results show that prior to the implementation of Mentimeter, most students had low initial abilities and low learning motivation. After the implementation of Mentimeter, there was a significant improvement in both understanding of the material and student motivation. The interactive use of Mentimeter successfully created a fun learning atmosphere and increased student engagement, particularly for students with a visual learning style. However, the study also faced limitations regarding device accessibility and time constraints, which affected the efficiency of Mentimeter usage. Based on the results, the use of Mentimeter can be an effective alternative to enhance learning motivation,